Spanish thinking about animals - Carretero González, Margarita, 1969- (Animal Turn Ser., 2020)
"Spanish Thinking about Animals brings together prominent scholars working on the expanding field of animal studies in Spain from a variety of disciplines within the humanities and social sciences, thus providing an interdisciplinary look at the animal question to an English-speaking audience"--